Influence of Maqian essential oil on gut microbiota and immunoresponses in type 1 diabetes: In silico study - Mahmoud Dahab; Hajo Idris; Ping Zhang; Mohammed Aladhadh; Eid A. Alatawi; Long Chiau Ming; Khang Wen Goh; Hooi-Leng Ser (Heliyon, 2024)
Diversity and homeostasis of gut bacterial composition is highly associated with the pathogenesis of insulin dysfunction and type 1 diabetes melittus (T1D), hence emerged in parallel with the activation of autoimmunity. We aimed to study the bioactive potential of essential oil from Zanthoxylum myriacanthum var. pubescens Huang (Maqian) through computational approaches. Twelve chemical constituents derived from Maqian essential oil were docked with selected proteins (i.e., 3pig, 1kho, 7dmq, 4m4d, 2z65, 4glp, and 3fxi) in which are involved in gut microbiota modulation in T1D. Subsequently, the prediction of bioavailability properties of the small molecules were evaluated. Among all chemical constituents, the post-docking interaction analysis demonstrated that α-phellandrene exhibits the strongest binding affinity and induces gut microbiota modulation with β-fructofuranosidase from Bifidobacterium longum. The current result revealed the potential of 3-Carene and α-Pinene in inducing specific changes in gut microbiota downregulating Clostridium perfringens and quenching Leptotrichia shahii respectively. β-Pinene possess exceptionally strong binding affinity that effectively disrupt the interaction between lipopolysaccharide and its cognate receptors, while α-Phellandrene was exhibited the uppermost binding affinity with TLR4/MD2 and could likely target TLR4 stimulating lipopolysaccharide. Our results are the first to report on the gut microbiota modulation effects of α-Phellandrene and β-Phellandrene via actions on LPS binding to CD14 and the TLR4 co-receptor signaling. In conclusion, our findings based on computational approaches, small molecules from Maqian present as promising agents which could regulate inflammatory response and modulate gut microbiota in type 1 diabetes mellitus.